Pelvic floor muscles contraction and sexual function are associated with hormonal treatment in women after breast cancer? - Conceição, Thais Martins Albanaz da; Roza, Thuane Da; Santos, Keyla Mara dos; Luz, Soraia Cristina Tonon da; Luz, Clarissa Medeiros da (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: Breast cancer has a high prevalence among women. It is known that breast cancer survivors can undergo a several alterations due to the treatment, including sexual dysfunction. Objective: This study aimed to determine the incidence of sexual dysfunction in women after breast cancer surgery, and assess the relationship between sexual dysfunctions and pelvic floor muscles (PFM) contraction, as well to verify if hormone therapy caused long-term occurrence of PFM weakness or sexual dysfunction. Methods: The sample was composed by 26 women with 48.4 ± 6.8 years which using hormone therapy treatment at least six months. Data on sexual dysfunction were collected through the Female Sexual Function Index- FSFI questionnaire and a section composed by demographic information. Furthermore, the PFM contraction was assessed using the PERFECT scale. Results: The results demonstrated a high rate of sexual dysfunction (64.3%) and a weak PFM contraction (2.31±1.3) among the women. In addition, a long-term hormone therapy had a negative association with PFM endurance and with the orgasm and satisfaction domains of the FSFI questionnaire. Conclusion: women using hormone therapy after breast cancer surgery had a high rate of sexual dysfunction and the long-term treatment of hormone treatment can be associated with a worsening of orgasm and sexual satisfaction in these women. Also, the use at long-term of hormone therapy had a negative association with the PFM endurance.